Development of competency models for the optimal strategy to enhance construction waste recycling implementation : a case study in malaysia - Omer, Mazen Mohamed Alkhdar (2024)
The continuous increase in construction projects worldwide has led to a corresponding increase in construction waste (CW). This has become a major concern as a significant amount of CW ends up in landfills, which can have critical impacts on both the economy and the environment if not properly managed. Previous works showed that the improper disposal of CW can lead to soil and water pollution, as well as the depletion of natural resources. Also, the accumulation of CW in landfills can contribute to greenhouse gas emissions and global warming. Therefore, it is imperative to address this issue by implementing construction waste recycling (CWR). As various strategies target the enhancement of CWR implementation, stakeholders face difficulties in selecting the right strategies. In this regard, two systematic literature reviews identified the list of CWR enhancement strategies and competencies for the optimal strategy. Therefore, three questionnaire surveys for three research phases were developed. The first survey belongs to research phase one, the second survey belongs to research phase two, and the third survey belongs to research phase three. The research targets construction industry professionals (e.g., project managers, civil engineers, and quantity surveyors) in Malaysia to gather their perceptions regarding the three phases. Moreover, research phase one was harnessed to identify the optimal strategy, phase two was used to develop a competency model for adopting the optimal strategy, whilst phase three was employed to determine the competency gap of the construction industry professionals using the developed model. In this context, a total of 108 responses were collected for phase one, and 120 survey participants for phase two. Also, 120 usable responses for phase three. The gathered data were analyzed through mean ranking, normalized value (NV), agreement analysis, factor analysis, usability analysis, and fuzzy synthetic evaluation (FSE) were harnessed to identify the optimal strategy within phase one. While latent class analysis (LCA) and partial least squares structural equation modelling (PLS-SEM) were used to develop the competency model in phase two. In addition, competency gap analysis and FSE were used to determine the competency gap in phase three. Research phase one identified ‘identifying construction activities that produce recyclable materials’ as the optimal enhancement strategy for CWR implementation. In contrast, phase two developed four competency models (models A, B, C, and D) for adopting the CWR optimal enhancement strategy. Besides, research phase three determined the competence gap level of the construction industry professionals on the developed competency models, which is 78.60%, 80.42%, 81.15, and 81.02% for Models A, B, C, and D, respectively. Also, FSE indicates that competence gap levels for each model are inclined to high competence. It is concluded among research phases two and three that Models B and D are the most appropriate. The mentioned models were statistically valid and practically have the lowest competency gap. Therefore, those models will assist the related parties of CWR in construction projects in enhancing their recycling rate. This research provides new insight from the perspective of construction industry professionals for enhancing the implementation rate of CWR. This research can help policymakers to generate new policies or regulations for better implementation of CWR. Furthermore, this work’s findings may serve as a fresh reference and can be a toolkit for construction players to enhance decision-making toward CWR